Pipocados: as sete pipocas capitais. - - Scota, Marcela da Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Nowadays, the contact with images, especially moving images, is very common in our society. Colors, shapes, textures and sounds form the visual elements that give power to convey information and/or entertainment to animations. Pipocados - The 7 Deadly Popcorns is an animated webserie, set in a fictional world inhabited by corn kernels, whose episodes will portray the transformation of corn into popcorn, using as a motto the seven deadly sins (gluttony, sloth, lust, pride, greed, wrath and envy). They were developed in animation and illustration softwares, with original sound design, and released in an online environment

Atualmente, o contato com imagens, sobretudo imagens em movimento, é muito frequente em nossa sociedade. Cores, formas, texturas e sons formam os elementos que inserem à animação o poder de transmitir informações e/ou entretenimento. Pipocados - As 7 Pipocas Capitais é uma websérie animada, ambientada num mundo fictício habitado por milhos, cujos episódios retratarão a transformação do milho em pipoca, utilizando como mote os sete pecados capitais (gula, preguiça, luxúria, soberba, avareza, ira e inveja). Foram desenvolvidos em softwares de animação e ilustração, com sound design originais, e divulgados em ambiente online
Keywords: Pecados capitais; Animação (Cinematografia); Milho de pipoca; Desenho industrial; Animation (Cinematography)